To Study Challenges and Strategies in Virtual Project Management: Examining Team Collaboration and Employee Engagement in Corporate Settings - Raorane, Sulbha S. (Journal of Neonatal Surgery, 2025)
This research paper explores the challenges and opportunities associated with Virtual Project Management (VPM) in corporates, particularly in the context of the increasing trend of remote work. The study investigates the effectiveness of virtual teams, the impact of communication tools, employee engagement, and the challenges of collaboration compared to traditional teams. A structured questionnaire was administered to 30 virtual project team members across various corporates, and hypothesis testing revealed significant difficulties in collaboration within virtual teams. The study concludes with recommendations for enhancing VPM efficiency and strategies for motivating virtual teams.